Notes to think about sexual diversity among the native people of Argentine Patagonia (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2022)
From the theoretical perspectives of feminisms that we could delimit as postcolonial, decolonial, and from Abya Yala, we propose to start investigating the ways in which sex / gender relations were organized among the original peoples of Argentine Patagonia. We delimit two activities to begin this path: identify the theories from which sexual diversity is analyzed in different theoretical contexts and carry out a rereading of documentary sources. In the analysis of documentary material we focused on: hygienist positivism and diffusionism -which related homosexuality to matriarchy- in the last century; We also incorporate current contributions that ask about the universality of male / female binarism. In the internal rereading and analysis of the documentary sources, we began to find indications to delve into the links between women and the so-called “fagots” in colonial records.
Keywords: Feminisms; Sexual Diversity; Native peoples; Shamanism